The hypoxia-induced microRNA-130a controls pulmonary smooth muscle cell proliferation by directly targeting CDKN1A. (April 2015) - Brock, Matthias; Haider, Thomas J.; Vogel, Johannes; Gassmann, Max; Speich, Rudolf; Trenkmann, Michelle; Ulrich, Silvia; Kohler, Malcolm; Huber, Lars C.
Graphical abstract: Highlights: In this study, the hypoxia-induced model of pulmonary hypertension was employed. Hypoxia increases the expression of the microRNA family miR-130. miR-130 directly targets the tumor suppressor CDKN1A/p21 in vitro and in vivo . Decreased expression of CDKN1A/p21 contributes to right ventricular hypertrophy. Inhibition of miR-130 by seed blockers might offer novel therapeutic options. Abstract: Excessive proliferation of human pulmonary artery smooth muscle cells (HPASMC) is one of the major factors that trigger vascular remodeling in hypoxia-induced pulmonary hypertension. Several studies have implicated that hypoxia inhibits the tumor suppressor p21 (CDKN1A). However, the precise mechanism is unknown. The mouse model of hypoxia-induced PH and in vitro experiments were used to assess the impact of microRNAs (miRNAs) on the expression of CDKN1A. In these experiments, the miRNA family miR-130 was identified to regulate the expression of CDKN1A. Transfection of HPASMC with miR-130 decreased the expression of CDKN1A and, in turn, significantly increased smooth muscle proliferation. Conversely, inhibition of miR-130 by anti-miRs and seed blockers increased the expression of CDKN1A. Reporter gene analysis proved a direct miR-130–CDKN1A target interaction. Exposure of HPASMC to hypoxia was found to induce the expression of miR-130 with concomitant decrease of CDKN1A. These findings were confirmed in the mouse model of hypoxia-induced pulmonary hypertension showing that the use of seed blockers against miR-130 restored the expression of CDKN1A. These data suggest that miRNA family miR-130 plays an important role in the repression of CDKN1A by hypoxia. miR-130 enhances hypoxia-induced smooth muscle proliferation and might be involved in the development of right ventricular hypertrophy and vascular remodeling in pulmonary hypertension.